A solid self-nanoemulsifying system of the BCS class IIb drug dabigatran etexilate to improve oral bioavailability. (July 2016) - Chai, Fujuan; Sun, Linlin; Ding, Yafei; Liu, Xiaoqing; Zhang, Yajie; Webster, Thomas J; Zheng, Chunli
Aim: To develop dabigatran etexilate (DE)-loaded self-nanoemulsifying drug delivery systems (SNEDDS) for the prevention of stroke and thromboembolism.Materials & methods : SNEDDS were optimized by ternary phase diagrams and then further solidified into dispersible tablets. In vitro dissolution was analyzed by a phase distribution study. In situ absorption and in vivo pharmacokinetic studies were tested in male Sprague-Dawley rats.Results: The phase distribution study showed that more than 60% of DE was retained in the oil phase. Dissolution rate was dramatically enhanced without significant precipitation (<30%) in simulated intestinal fluid. Optimized SNEDDS had 531.80% relative bioavailability compared with Pradaxa ® capsules (a commercial DE product).Conclusion: The developed SNEDDS are promising materials for improving the dissolution and oral bioavailability of BCS class IIb drugs.